Statistical screening of medium components for lactic acid production from tapioca starch hydrolysate by Lactobacillus casei TISTR 453 using Plackett-Burman design - Samansoranakun, Chayaporn; Adthalungrong, Chaowaree (Asia-Pacific Journal of Science and Technology, 2017)
Plackett-Burman design was employed for efficiently screening and selection of medium components for lactic acid production by Lactobacillus casei TISTR 453 using tapioca starch hydrolysate as a carbon source in a minimal numbers of experiments. A total of 16 experiments were conducted to determine the significance of 13 nutrient parameters on lactic acid production. All experiments were carried out in a submerged fermentation for 96 h at 34 oC under static condition. An initial level of reducing sugar from tapioca starch hydrolysate was applied at 120 g/l. From the results, the highest lactic acid concentration at 73.00 g/l was obtained. From the regression analysis output, 10 out of 13 parameters studied were found to influence lactic acid production significantly. However, too many parameters would lead to a difficulty on medium optimization in the subsequent steps. Therefore, only 4 medium components namely winery yeast disposal, peptone, meat extract and dipotassium hydrogen phosphate were chosen for further optimization since they were previously reported as important factors on lactic acid fermentation. The other 4 components which showed significant results including calcium carbonate, triammonium citrate, manganese sulfate monohydrate, and sodium acetate were to be assigned as fixed variables of fermentation medium in medium optimization steps. On the other hand, corn steep liquor and ammonium sulfate were disregarded, although they provided significant results on lactic acid production, since their main effects were negative.